The Integrative Effects of Leading by Example and Follower Traits in Public Goods Game: A Multilevel Study - Qiu, Huiqing; Zhang, Youlan; Hou, Gonglin; Wang, Zhongming (Frontiers in Psychology, 2018)
As an important way to understand leadership based on voluntary contribution mechanisms, the importance of leading by example to teamwork is becoming more and more evident in recent years. However, existing theories based on signaling and reciprocity perspectives respectively provide incomplete theoretical explaining. This study adds clarity by conducting a cross-level study that indicates a possible integrative framework of both signaling and reciprocity perspective on leading by example. Results were using data gathered from 130 Chinese college students, which were allocated into one baseline group and three experimental groups. A hierarchical model was used to examine the effects of leading by example on different levels. It is found that leading by example has positive effects on the cooperation of followers on both the group level and the individual level. Risk attitudes and trust attitudes have positive effects on the cooperation of followers while Machiavellianism has no significant effects. Our findings suggest that both leading by example and personal traits significantly influence cooperation but on different levels. It also reminds us that a more systematic way to understand leadership is needed.